2023
DOI: 10.1042/cs20230499
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine protects against the development of experimental abdominal aortic aneurysm

Yi Zhao,
Qi-Rui Shen,
Yu-Xin Chen
et al.

Abstract: Abdominal aortic aneurysm (AAA) is characterized by at least 1.5-fold enlargement of the infrarenal aorta, a ruptured AAA is life-threatening. Colchicine is a medicine used to treat gout and familial Mediterranean fever, and recently it was approved to reduce the risk of cardiovascular events in adult patients with established atherosclerotic disease. With an AAA mice model created by treatment with porcine pancreatic elastase (PPE) and beta aminopropionitrile (BAPN), this work was designed to explore whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…When colchicine was given at late stage when AAA was already established, colchicine lost its inhibitory role 2 , 20 . In contrast, when colchicine was given at the first day of BAPN and elastase application combination-induced AAA, the same drug showed a potent a potent limitation of AAA growth 18 . We and others further demonstrated that early use of colchicine prevented AAA development and rupture in several AAA models, for example, Ang-II infusion, calcium chloride and calcium phosphate application 19 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…When colchicine was given at late stage when AAA was already established, colchicine lost its inhibitory role 2 , 20 . In contrast, when colchicine was given at the first day of BAPN and elastase application combination-induced AAA, the same drug showed a potent a potent limitation of AAA growth 18 . We and others further demonstrated that early use of colchicine prevented AAA development and rupture in several AAA models, for example, Ang-II infusion, calcium chloride and calcium phosphate application 19 .…”
Section: Discussionmentioning
confidence: 89%
“…Studies reported that daily administration of colchicine did not significantly limit AAA growth 20 . Yet, evidence form us and those from others suggested a therapeutic role of colchicine on AAA 18 , 19 . Although we do not have exact explanation for these conflicting results, differences in AAA models and the time point of colchicine administration may account for these observations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It showed success in preventing atherosclerotic cerebrovascular disease. Zhao et al ( 81 ) conducted an animal study that demonstrated the protective effect of colchicine against the development of experimental abdominal aortic aneurysms. However, Phie et al ( 82 ) suggested that colchicine lacked efficacy in reducing the growth of abdominal aortic aneurysms in a mouse model.…”
Section: Potential Drug Therapy Approaches In Intracranial Aneurysmsmentioning
confidence: 99%